Evaluasi Kadar Oksibenzon dalam Sediaan Lotion Tabir Surya yang Beredar di Pasar Modern Menggunakan Spektrofotometri Ultraviolet - Herman Widjaja; Arnoldus Christian Waani (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Cosmetics are a mixture of chemical compounds from natural and synthetic materials used for skin care. One of the widely used cosmetic products is sunscreen which functions to protect the skin from Ultraviolet (UV) radiation. Oxybenzone is an active ingredient commonly used as a UV absorber, but its use is limited by regulations due to potential side effects. This study aims to evaluate the levels of oxybenzone in commercial sunscreen lotions circulating in the modern market using the UV-Vis spectrophotometry method. The analysis was carried out at a maximum wavelength (λmax) of 288 nm with the standard curve method, after optimization of the operating time. Measurements were carried out in replication to ensure data validity. The study samples consisted of three commercial sunscreen lotion products widely circulating in the modern market. The results of the analysis showed that the average oxybenzone levels in sample A were 6.7 ± 0.0107%, sample B was 6.03 ± 0.0104%, and sample C was 2.34 ± 0.0060%. All samples remained below the maximum limit set by the Indonesian Food and Drug Monitoring Agency (BPOM), which is 10%. These results indicate that the tested products still meet the safety requirements for the active ingredient oxybenzone. These findings underscore the importance of regular cosmetic quality control to ensure regulatory compliance and consumer safety.